Ethical considerations of corporate social responsibility - A South African perspective - B. Ackers (South African Journal of Business Management, 2015)
Today, companies are under increasing pressure to implement corporate social responsibility [CSR] programmes that account for the economic, social and environmental impacts of their operations. In addition to companies voluntarilywanting to be seen as responsible corporate citizens, the requirement for CSR reporting is being institutionalised by the King Code of Governance [King III] in South Africa. The application of King III is mandatory for all companies listedon the Johannesburg Stock Exchange [JSE], albeit on an 'apply or explain' basis. King III requires companies to not only disclose their CSR performance, but also to ensure that such disclosures have been independently assured. Irrespective ofthe underlying reason for companies disclosing their CSR performance and for providing independent assurance thereon, companies are moving away from simplistically applying the cliche attributed to Friedman that "the social responsibility of business was to use its resources to engage in activities that would increase profits". Companies that have traditionally provided financial reporting to shareholders, are now beginning to account for their non-financial performance to other stakeholders as well. This paradigm shift requires those charged with company governance and reporting (including accounting professionals usually associated with financial reporting), to re-examine their morals, values and ethical beliefs.
Keywords: 650